2020
DOI: 10.1063/5.0008949
|View full text |Cite
|
Sign up to set email alerts
|

Noise characterization of ultrasensitive anomalous Hall effect sensors based on Co40Fe40B20 thin films with compensated in-plane and perpendicular magnetic anisotropies

Abstract: We have performed magnetotransport and noise characterization studies of ultrasensitive anomalous Hall effect (AHE) sensors based on the Ta/Co40Fe40B20/MgO multilayer structure. The magnetization is near spin reorientation transition. This greatly reduces the saturation field with improvement of the magnetic sensing performance. We have performed temperature-dependent measurements to investigate the effect of tunable magnetic anisotropy. Both 1/f noise and sensitivity have a strong temperature dependence. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The competition between the two can, in fact, reduce the field detectability. In our recent studies on Ta/Co 40 Fe 40 B 20 /MgO [ 5 ] and MgO/Co 40 Fe 40 B 20 /Ta/Co 40 Fe 40 B 20 /MgO [ 2 ] systems, we found that anomalous Hall sensors have the best performance when the magnetization is tuned to be near the spin-reorientation transition. In Ta/Co 40 Fe 40 B 20 /MgO [ 5 ], the field detectability reaches 76 nT/√Hz at 1 Hz and 2 nT/√Hz at 10 kHz at a perpendicular bias field of −12 Oe.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The competition between the two can, in fact, reduce the field detectability. In our recent studies on Ta/Co 40 Fe 40 B 20 /MgO [ 5 ] and MgO/Co 40 Fe 40 B 20 /Ta/Co 40 Fe 40 B 20 /MgO [ 2 ] systems, we found that anomalous Hall sensors have the best performance when the magnetization is tuned to be near the spin-reorientation transition. In Ta/Co 40 Fe 40 B 20 /MgO [ 5 ], the field detectability reaches 76 nT/√Hz at 1 Hz and 2 nT/√Hz at 10 kHz at a perpendicular bias field of −12 Oe.…”
Section: Introductionmentioning
confidence: 94%
“…Anomalous Hall sensors are magnetic sensors that take advantage of the anomalous Hall effect of ferromagnets [ 1 , 2 , 3 , 4 , 5 , 6 ]. Electrons with different spins, under the spin–orbit interaction, deflect towards opposite transverse directions when a longitudinal electric current is applied [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations